Menciptakan Generasi Muda tanpa Pernikahan Dini di Kabupaten Situbondo - Arif Aminullah Prayono, Alfanda Rahmatullah (Forum Ilmu Sosial, 2016)
Figures early marriage in Situbondo, especially in Sub Arjasa fairly high. The high rates of early marriage are backed by many factors, the most dominant cultural factors with proven already become hereditary. Early marriage can be defined as two people of the opposite sex who was a teenager in a family. Early marriage to the attention of many parties in view of the risks arising from early marriage is sex in young people, infectious diseases, and mental and emotional unstable that may be causing a conflict. This study used qualitative methods, namely descriptive analysis, in which the author wants to explain or describe some viewpoints about the wedding themselves, that is, from the standpoint of culture in Situbondo, Islamic religious viewpoint, and the viewpoint of the law of Indonesia. The purpose of this study was to describe as well as a consideration for the people who still impose early marriage without looking at other aspects. The result of this research is the prevention of early marriage is very important for people, especially for teenagers today. Besides beneficial to oneself, is also beneficial to avoid a negative view of society. Prevention of early marriage also want to form young people who are aware of education. Basically, getting married has become the family's privacy, or yourself. But in education, we are aware of what we should do. Society and youth in the prevention of early marriage is encouraged to have the awareness to improve human resources optimally through education.